2019
DOI: 10.1103/physrevapplied.11.064031
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Electric-Current-Limiting and Photodetection Effect in Two-Dimensional Hydrogenated Borophene

Abstract: The electronic transport and photoelectric properties of hydrogenated borophene B4H4, which was realized in a recent experiment by Nishino, et al. [J. Am. Chem. Soc. 139, 13761 (2017)], are systematically investigated using the density functional theory and non-equilibrium Green's function methods. We find that B4H4 exhibits a perfect current-limiting effect and has high (along the zigzag direction) and low (along the armchair one) optional levels due to its strong electrical anisotropy. Moreover, B4H4 can gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 57 publications
4
30
0
1
Order By: Relevance
“…Besides, both the energy dispersions and effective mass become anisotropic away from Γ point, such as between the x-axis (along zigzag direction) and y-axis (along armchair direction) shown in Fig. 1a, which should lead to anisotropic transport properties along these two directions like many other 2D materials 6,[38][39][40] . Note that the bandgap becomes smaller (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, both the energy dispersions and effective mass become anisotropic away from Γ point, such as between the x-axis (along zigzag direction) and y-axis (along armchair direction) shown in Fig. 1a, which should lead to anisotropic transport properties along these two directions like many other 2D materials 6,[38][39][40] . Note that the bandgap becomes smaller (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4) to its Z-type diode. The current along the A direction is slightly smaller than that along the Z direction due to larger carrier effective mass along A direction, implying its weak anisotropy ratio (1.3) 40 .…”
Section: Spin Transport Properties and Pn-junction Diodes Of Mnbi 2 Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that hydrogen boride sheets have a high H 2 content (8.5 wt %) [2], unique electronic properties [3,4], solid acid catalytic properties [5,6], photoinduced hydrogen release capability [7], and a unique ability to reduce metal ions to form nanocomposites [8][9][10]. In addition, theoretical models and computer simulations demonstrate that borophane is a promising candidate for applications such as anode material, alcohol gas sensors, current limiters, and photodetectors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although GSJ can make graphene to be gapless, it still has a great demand to have alternative 2D semiconductors having both high mobility and finite band gap for the applications of electronics. Blue phosphorus (BlueP) and black phosphorus [15][16][17][18][19][20][21][22][23], which have both ultra-high mobility and finite band gap (2.0 eV and 0.5 eV, respectively), can satisfy the above mentioned properties [24]. Theoretical computations with external stimuli such as application of an electric field and surface functionalization [25] on the electronic properties of BlueP have also been conducted to explore the effects of doping [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%